Fiqh Bi'ah Analysis on Social Environmental Audit - Hilal, Syamsul; Sisdianto, Ersi (MALIA: Journal of Islamic Banking and Finance, 2024)
This research aims to analyze the application of Fiqh Bi'ah (Islamic environmental fiqh) in environmental social auditing practices, focusing on how Islamic principles can improve environmental accountability and sustainability. Using qualitative research methods, the object of this study includes the application of Fiqh Bi'ah principles in environmental social auditing. The data collection techniques used are interviews, observation, and document analysis, with data analysis through data reduction, verification, and conclusion drawing. The results show that the application of Fiqh Bi'ah principles, such as khilafah (guardian of the earth), mizan (balance), as well as the prohibition of fasād (destruction) and isrāf (waste), strengthen the moral and ethical framework in environmental auditing. The limitations of this study lie in the limited sample size and less generalizability of the findings beyond the university context. The novelty of this study theoretically combines Islamic teachings with environmental auditing practices, and practically provides guidance in improving environmental accountability based on Islamic values. It is recommended that organizations incorporate Fiqh Bi'ah principles, such as khilafah, mizan, and the prohibition of fasād and isrāf, into their environmental auditing frameworks to enhance accountability and sustainability in line with Islamic ethical values